Evaluation of the Rationality of the Use of Antibiotics in Paediatric Diarrheal Patients in Hospital Inpatient Facilities in the City of Bandung - Linda Purnamawati Suherman; Intan Wulan Putri Pratama; Eni Margayani; Vidya Rachmawati (Journal of Pharmascience, 2026)
Diarrhoea in children is often associated with irrational antibiotic use, even though the cause is not bacterial infection. Excessive antibiotic use can increase antibiotic resistance, a significant problem in healthcare. This study aimed to evaluate the rationality of antibiotic use in paediatric inpatients with diarrhoea at a single hospital in Bandung, including demographic characteristics, types of antibiotics used, and appropriate indication, drug selection, dosage, and administration intervals. This study was observational, using a non-experimental descriptive analysis design. Data collection was conducted retrospectively from January to December 2024. Out of a total population of 229 patient medical records, 54 patient medical records met the inclusion criteria and were used as the study sample. The rationality of drug use refers to the Indonesian Ministry of Healthâ€™s guideline. The results showed that 55.6% of patients were male, with toddlers (46.2%) being the largest age group. Ceftriaxone was the most commonly prescribed antibiotic (24%). The rationality of antibiotic use was 100% for indications and drug selection, 94.4% for dosage, and 90.7% for the interval between doses. However, the identified discrepancies in dosage (5.6%) and administration intervals (9.3%) require immediate attention to minimize the risk of therapeutic failure and antibiotic resistance.Â